The relationship between hope in healthcare employees and social support and coping ability during the outbreak process - Kazgan, Asli; Yildiz, Sevler; Kurt, Osman (Bayrakol Medical Publisher, 2021)
Aim: In this study, it was aimed to examine the relationship between the concept of hope that is present in healthcare professionals during the COVID-19 pandemic process and the possible relationship between perceived social support and coping ability. Material and Method: Sociodemographic and Clinical Data Form, State-Trait Anxiety Inventory (STAI), Trait Hope Scale (THS), Multi-Dimensional Perceived Social Support Scale (MDPSSS), Coping with Stress Scale (CSS) were applied to 170 healthcare professionals working in the pandemic hospital and meeting the study criteria. Results: The THS score was found to be the lowest in those working in both the service and emergency service/polyclinic, and a statistically significant difference was found between this group and those working in the service and those working in the emergency/outpatient clinic (p<0.001). The MDPSSS score of the group working in both departments was the lowest and this decrease was statistically significant (p=0.002). THS scores of the doctors were lower than nurses, and this lowness was statistically significant (p=0.001). A positive significant correlation was found between the total score of THS and CSS and MDPSSS scores (r=0.226, p=0.003) (r=0.194, p=0.023). Discussion: Perceived social support and hope levels decrease as the number of working units of health personnel increases during the Covid-19 pandemic process. Levels of hope differ according to the professions. The level of hope is positively associated with the coping ability and perceived multi-dimensional social support. This study has revealed that functional coping attitudes and perceived social support in healthcare professionals during pandemic periods are associated with high levels of hope.
Keywords: Social support; Coping ability; COVID-19; Healthcare workers; Hope concept